2014
DOI: 10.4103/0975-962x.144717
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the MSX1 gene in Turkish children with non-syndromic tooth agenesis and other dental anomalies

Abstract: Aim:To search for mutations on the MSX1 gene and to present a genetic basis for non-syndromic tooth agenesis in conjunction with dental anomalies in a Turkish population.Materials and Methods:The patients included in this study were otherwise healthy, with ages ranging from seven to eighteen years. Eighty-two of them had one to six teeth missing (Group I) and 26 had more than six teeth missing (Group II), except for the third molars,. The missing teeth and dental anomalies were examined clinically and radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
5
1
1
Order By: Relevance
“…Evaluation of root shape of upper and lower incisors in this study demonstrated that individuals with third molar agenesis and those with agenesis of premolars or lateral incisors had different root morphology for upper and lower incisors from those individuals without tooth agenesis. These findings are at odds with those of a previous study where, after evaluation of root resorption of lateral incisors, there was no apparent association between root shape and genetic factors, even though the evaluation of root shape was not within the scope of the study 22 and considering that tooth agenesis has a genetic etiology [2][3][4] .…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Evaluation of root shape of upper and lower incisors in this study demonstrated that individuals with third molar agenesis and those with agenesis of premolars or lateral incisors had different root morphology for upper and lower incisors from those individuals without tooth agenesis. These findings are at odds with those of a previous study where, after evaluation of root resorption of lateral incisors, there was no apparent association between root shape and genetic factors, even though the evaluation of root shape was not within the scope of the study 22 and considering that tooth agenesis has a genetic etiology [2][3][4] .…”
Section: Discussioncontrasting
confidence: 88%
“…Tooth agenesis is complex, and its heterogeneous characteristics are apparently associated with other dental changes 1 . The etiology of tooth agenesis involves mutations in certain genes such as MSX1 and PAX9, and genes such as WNT10A appear to play an important role in odontogenesis [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…MSX1 interacts with β-catenin to inhibit the cell proliferation mediated by WNT signaling pathways (10). MSX1 mutation is involved in the congenital lack of teeth (tooth agenesis or hypodontia), limb deficiency, craniofacial bone morphogenesis and cleft lip, but few studies have examined its role in tumorigenesis (11)(12)(13)(14)(15)(16). Previous studies suggest that the deregulated expression of MSX1 is…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the MSX1 gene produce specific oligodontia, which are of particular interest to second premolars and third molars [ 49 , 50 ]. Thus, the Arg31Pro mutation of the MSX1 gene was associated with second premolars agenesis, and the Ser105Stop mutation of the MSX1 gene was associated with premolar hypodontia and orofacial cleft [ 51 , 52 , 53 , 54 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%